FENOMENA DIPLOMASI MEDIA SOSIAL: KETIKA NEGARA BERPERANG LEWAT NARASI DIGITAL - Naisya Audina (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The rise of social media has shifted diplomatic practice from a conventional, elitist, and closed model toward an open, rapid, and participatory digital communication space. In this context, narratives no longer function merely as communication tools but as instruments of non-military power that shape perceptions, legitimacy, and a state’s position in the international arena. This article analyzes how developing countries in Southeast Asia utilize social media as a space for the production and contestation of strategic narratives to build national image, maintain legitimacy, and respond to the dominance of global narratives often shaped by major powers. The study employs a qualitative approach using the strategic narratives framework combined with the concepts of soft power and digital public diplomacy. Data are drawn from documentary analysis of official social media accounts of foreign ministries, heads of state, and diplomatic missions, as well as relevant literature review. The findings indicate that the digital narrative diplomacy of developing countries tends to be defensive in responding to regional geopolitical issues, accompanied by limited offensive efforts to construct national identity and international legitimacy. Limitations in digital infrastructure, the dominance of global platform algorithms, and gaps in human resource capacity pose significant challenges to expanding the reach of these narratives. The study implies a shift in the arena of power from material power to narrative power in digital spaces and highlights the urgent need for developing countries to strategically and ethically manage digital diplomacy through the mastery of strategic narratives in contemporary international relations.